Andragogue Roles Expression Modern Society - Trakšelys, Kęstutis; Andriekienė, Rūta Marija (Pedagogika, 2016)
The article reveals and analyzes the heterogenic roles of andragogues in the nowadays changing adult education reality. Today we can meet the elements of andragogue’s activities in various sectors and social fields: vocational education and training, continuing vocational training, professional and social integration, institutions and organisations providing in-service training for staff, adult education, various administrative structures, associations, leisure clubs, health education, social work, colleges, universities, institutions that are dealing with informally or non-formally acquired learning outcomes validation, providing counselling or information services, etc. Thus, the andragogue’s profession is not legitimized yet and there is no andragogue’s position, we have to discuss the roles that are really performed and their expression in other positions. The article consists of two chapters. The Chapter One analyzes various roles realized by andragogue: andragogue lecturer, organizer, analyst, counsellor, and tutor. There are efforts based on scientific literature analysis and praxeological andragogues’ activities investigations in order to justify the roles performed by andragogue. The Chapter Two is dedicated to the real expression of the andragogue’s performance roles in different positions of adult education actor. It is assumed that this factor makes andragogues’ professionalization more difficult, there is a need to legitimize the profession.